2023
DOI: 10.18280/ijsdp.180120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Interrelationships Among Key Stakeholders’ Performance in Achieving Project Success

Abstract: Poor performance of key stakeholders contributes to project problems such as delays, cost overruns, inferior quality, work accidents, etc. Many studies have evaluated the correlation between stakeholders and project success; however, no research has been conducted to evaluate the interrelationships among their performances, i.e how one stakeholder's performance affects the other(s) and ultimately determines the project's success. This study aims to fill this gap. A conceptual model was developed using the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several studies have shown that stakeholder characteristics determine the decision-making process and development process. The community has much discussion but only involves citizens who are most motivated and voluntarily to participate, involving people who are better off in terms of income, education, and status [50][51][52][53][54][55][56].…”
Section: Factors Affecting Stakeholders' Communication In Pdpmentioning
confidence: 99%
“…Several studies have shown that stakeholder characteristics determine the decision-making process and development process. The community has much discussion but only involves citizens who are most motivated and voluntarily to participate, involving people who are better off in terms of income, education, and status [50][51][52][53][54][55][56].…”
Section: Factors Affecting Stakeholders' Communication In Pdpmentioning
confidence: 99%